2021
DOI: 10.1371/journal.pone.0256932
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms among frontline and non-frontline healthcare providers in response to the COVID-19 pandemic in Kelantan, Malaysia: A cross sectional study

Abstract: Background Healthcare providers are vulnerable in the fight against COVID-19 and may experience significant psychological and mental health consequences. This study aimed to compare the levels of depressive symptoms among frontline and non-frontline healthcare providers in response to the COVID-19 pandemic. Methods A comparative cross-sectional study was conducted in two government hospitals managing COVID-19-related cases in Kelantan, Malaysia from May to July 2020 to identify and compared depressive sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
3
10
2
Order By: Relevance
“…HCWs who have acquired the necessary knowledge, skills, and training to manage COVID-19 patients with a lower risk of psychological distress [ 53 ]. Similar to the present study, Norhayati et al [ 54 ] conducted a local study in Kelantan, comparing depressive symptoms among frontline and non-frontline HCWs. Norhayati et al [ 54 ] found that non-frontline HCWs exhibited higher depressive symptoms (37.7%) than frontline healthcare providers (27.5%).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…HCWs who have acquired the necessary knowledge, skills, and training to manage COVID-19 patients with a lower risk of psychological distress [ 53 ]. Similar to the present study, Norhayati et al [ 54 ] conducted a local study in Kelantan, comparing depressive symptoms among frontline and non-frontline HCWs. Norhayati et al [ 54 ] found that non-frontline HCWs exhibited higher depressive symptoms (37.7%) than frontline healthcare providers (27.5%).…”
Section: Discussionsupporting
confidence: 60%
“…Similar to the present study, Norhayati et al [ 54 ] conducted a local study in Kelantan, comparing depressive symptoms among frontline and non-frontline HCWs. Norhayati et al [ 54 ] found that non-frontline HCWs exhibited higher depressive symptoms (37.7%) than frontline healthcare providers (27.5%). These findings further highlight the importance of not neglecting the mental health of HCWs who are not directly involved with caring for COVID-19 patients.…”
Section: Discussionsupporting
confidence: 60%
“…All the items were rated on a four-point scale scoring from 0 (not at all) to 3 (nearly every day). The total score ranges from 0 to 21, and symptom severity was interpreted as follows: absence of anxiety (0-4), mild anxiety (5)(6)(7)(8)(9), moderate anxiety (10)(11)(12)(13)(14), and severe anxiety (15)(16)(17)(18)(19)(20)(21). Though initially designed to identify generalized anxiety disorder (GAD), the GAD-7 has also been considered as a good screening tool for other common anxiety disorders.…”
Section: • Gad-7mentioning
confidence: 99%
“…In a recent systematic review of updated prevalence estimates for depression and anxiety from 65 studies, Yufei Li showed a high prevalence of moderate depression and anxiety among health care workers across 21 countries during the COVID-19 pandemic [10], which can negatively impact on the quality of COVID-19 patient care [11]. In Southeast Asia alone, recent evidence has revealed that there seems to be an increasing trend for anxiety and depression over time among healthcare workers compared to the first wave of COVID-19 [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation